2001
DOI: 10.2310/6650.2001.33898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexamethasone on TSH Secretion Induced by TRH in Human Obesity

Abstract: The sensitivity of the TSH secretory system to glucocorticoid inhibitory action is preserved in obese subjects with abnormally elevated TSH response to TRH, but not in subclinically hypothyroid obese patients. The TRH plus dex test might be useful in future studies to understand the mechanisms underlying alterations in TSH secretion in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…The first was on the pituitary level, indicated by lower TSH levels. This suppressive effect is in accordance with literature reports on effects of glucocorticoids [31,32] . The second effect was on the level of peripheral thyroid hormone metabolism reflected in changes in T 3 and rT 3 .…”
Section: Discussionsupporting
confidence: 81%
“…The first was on the pituitary level, indicated by lower TSH levels. This suppressive effect is in accordance with literature reports on effects of glucocorticoids [31,32] . The second effect was on the level of peripheral thyroid hormone metabolism reflected in changes in T 3 and rT 3 .…”
Section: Discussionsupporting
confidence: 81%
“…Meanwhile with respect to the post-DST statistically significant lower neopterin levels in the patient group, the suppressive effects of dexamethasone itself, a synthetic glucocorticoid with a long half-life, should be taken into consideration. Dexamethasone also suppresses other pituitary hormones including prolactin and thyroid-stimulating hormone (TSH) (Olazabal et al 2000;Coiro et al 2001). Second, it was reported that norepinephrine, a neurotransmitter frequently reported to be increased in PTSD, and the HPA axis might lead to the inhibition of cytokine secretion.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibitory effect of dexamethasone was used for monitoring of subclinical hypothyroidism in obese patients. Administration of TRH after dexamethasone increased the TSH level only in hypothyroid patients but not in euthyroid obese patients [23].…”
Section: Effects Of Glucocorticoids On Trh and Tsh Levelsmentioning
confidence: 99%